2004
DOI: 10.1007/s00335-004-2386-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of X-linked hybrid sterility in the house mouse

Abstract: Hybrid sterility is a common postzygotic reproductive isolation mechanism that appears in the early stages of speciation of various organisms. Mus musculus musculus and Mus musculus domesticus represent two recently separated mouse subspecies particularly suitable for genetic studies of hybrid sterility. Here we show that the introgression of Chr X of M. m. musculus origin (PWD/Ph inbred strain, henceforth PWD) into the genetic background of the C57BL/6J (henceforth B6) inbred strain (predominantly of M. m. do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
197
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(226 citation statements)
references
References 28 publications
25
197
2
2
Order By: Relevance
“…In hybrid males, sterility is more common when M. m. musculus is the mother (Britton-Davidian et al 2005;Good et al 2008b;Vyskočilová et al 2009). The role for the M. m. musculus X chromosome suggested by these observations has been confirmed through backcrosses (Storchová et al 2004) and chromosomal introgression studies (Good et al 2008a;Gregorová et al 2008). Reduced gene flow of X-linked loci across the hybrid zone (Tucker et al 1992;Dod et al 1993;Munclinger et al 2002;Payseur et al 2004;Dod et al 2005;Macholán et al 2007) raises the possibility that this chromosome also confers hybrid male sterility in natural populations.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…In hybrid males, sterility is more common when M. m. musculus is the mother (Britton-Davidian et al 2005;Good et al 2008b;Vyskočilová et al 2009). The role for the M. m. musculus X chromosome suggested by these observations has been confirmed through backcrosses (Storchová et al 2004) and chromosomal introgression studies (Good et al 2008a;Gregorová et al 2008). Reduced gene flow of X-linked loci across the hybrid zone (Tucker et al 1992;Dod et al 1993;Munclinger et al 2002;Payseur et al 2004;Dod et al 2005;Macholán et al 2007) raises the possibility that this chromosome also confers hybrid male sterility in natural populations.…”
mentioning
confidence: 83%
“…In addition, M. m. musculus and M. m. domesticus exhibit prezygotic isolation, including preferences for mates from the same subspecies (Laukaitis et al 1997;Talley et al 2001;Ganem 2002, 2005;Smadja et al 2004;Ganem et al 2008) and higher fertilization rates by sperm from the same subspecies when females are multiply mated (Dean and Nachman 2009). The most direct evidence for reproductive isolation comes from laboratory crosses involving wild-derived inbred strains, where F 1 hybrid male sterility is routinely observed, usually without hybrid female sterility (Iványi et al 1969;Forejt and Iványi 1974;Storchová et al 2004;BrittonDavidian et al 2005;Vyskočilová et al 2005Vyskočilová et al , 2009Good et al 2008a,b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic studies in Drosophila demonstrated an excess of hybrid sterility loci on the X chromosome, a phenomenon referred to as Flarge X-effect_ (Orr & Coyne 1989, Tao et al 2003. Several X-linked hybrid sterility loci were also reported in mice (Oka et al 2004, Storchova et al 2004. These genetic studies suggest that hybrid sterility might be caused by incompatibility of multiple loci (or genes).…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%